2003
DOI: 10.1099/vir.0.19035-0
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus infection of murine sensory ganglia induces proliferation of neuronal satellite cells

Abstract: Herpes simplex virus (HSV) is a virtually ubiquitous human pathogen that, following cutaneous infection, latently infects neurons of sensory ganglia. Satellite cells (SCs) ensheath and provide metabolic support for these neurons, and could potentially participate in controlling HSV disease. Although SCs are restrictive for HSV replication, hypercellularity of non-neuronal cells in ganglia is prominent during HSV infection in animal models. SCs proliferate in response to trauma, e.g. nerve cut or crush, but it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…1D and E). In both mock-and VZV-infected ganglia, the number of S100-expressing cells increased over time following explant, consistent with studies of mouse and rat sensory ganglia reporting that the process of explanting ganglia can induce satellite cell proliferation (6,28).…”
supporting
confidence: 67%
“…1D and E). In both mock-and VZV-infected ganglia, the number of S100-expressing cells increased over time following explant, consistent with studies of mouse and rat sensory ganglia reporting that the process of explanting ganglia can induce satellite cell proliferation (6,28).…”
supporting
confidence: 67%
“…In this case, proliferation started decreasing after this time-point [34]. Later, other BrdU incorporation studies showed that SGCs proliferate during Herpes Simplex virus infection, with increases up to 5 days of disease, the latest time point evaluated [35]. This was proposed to be part of a mechanism of neuronal survival during the disease [35].…”
Section: Discussionmentioning
confidence: 81%
“…Later, other BrdU incorporation studies showed that SGCs proliferate during Herpes Simplex virus infection, with increases up to 5 days of disease, the latest time point evaluated [35]. This was proposed to be part of a mechanism of neuronal survival during the disease [35]. The same group also found proliferation of SGC in an animal model of scarification of the skin, considered to be a model of minor tissue trauma [7].…”
Section: Discussionmentioning
confidence: 96%
“…It can be proposed that a breakdown of this barrier can lead to widespread infection of the ganglia. In DRG of HSV-infected mice there was a 3-fold increase in SGC compared with controls [44]. This proliferation could protect neurons against the virus or promote repair of damage in them.…”
Section: Sgcs and Herpesmentioning
confidence: 90%